Limites impostos pelo Direito Administrativo à utilização da Inteligência Artificial no serviço público de saúde - Sievers Junior, Fretz (2023)
With the advent of the digital revolution that triggered the emergence of the Internet in the world, the ease of spreading information emerged, leading to the emergence of Society 4.0, based on information systems, Internet of Things, Big Data, Artificial Intelligence, Science of Data and Augmented Reality, providing new treatments and procedures in the health area, through a source of patient data for machine learning and deep machine learning, to take care of man. In this context that society is going through, new problems arise in society that must be analyzed in the light of administrative legal principles. The work makes a bibliographical research on what Artificial Intelligence is, its applications in the health area and makes an analysis of the limits imposed by administrative law on the use of Artificial Intelligence in the public health service, in its application in its constitutional requirement of its principles, financial limitations and the optimization of administrative bodies, always aiming to do more with less, complying with the principle of efficiency, properly using the resources available in the health area, taking care of the most valuable asset of all citizens, life. The use of Artificial Intelligence is one of the possibilities for improving public services, aiming to serve the entire population with greater quality. Artificial Intelligence is being applied in many countries to manage public affairs, especially in the health area, bringing numerous benefits to the population